VERIFICATION OF TOPOGRAPHIC DRAWING PARAMETERS OF WATER OUTLETS AT EARTH DAMS (PANGEEA, 2025)
ABSTRACT. The verification of the topographic parameters at the structural components of the earth dams can be requested within the technical expertises. Actions in the foundation ground or those of a hydrological, hydraulic and seismic nature can influence over time the behaviour of some structural components of the earth dams. The case study prepared through a technical expertise on an earthen dam in the Moldova area highlighted a risk in the operation of the evacuator for high flows. The risk is also generated by a series of topographic features of the longitudinal profile identified by topographic measurements. Risk is also influenced by climate change through the formation of maximum flows not considered in design. The results obtained by the hydraulic simulation of the evacuator confirm a possible faulty behaviour of the connecting channel at the transit of the maximum flows. This situation required the creation of new topographic documentation to verify the construction.
Keywords: high flow outlet structure; technical expertise; longitudinal profile; risk